Does DNA methylation mediate the association of age at puberty with forced vital capacity or forced expiratory volume in 1 s?. Issue 1 (28th February 2022) - Li, Liang; Zhang, Hongmei; Holloway, John W.; Ewart, Susan; Relton, Caroline L.; Arshad, S. Hasan; Karmaus, Wilfried
Background: Age of pubertal onset is associated with lung function in adulthood. However, the underlying role of epigenetics as a mediator of this association remains unknown. Methods: DNA methylation (DNAm) in peripheral blood was measured at age 18 years in the Isle of Wight birth cohort (IOWBC) along with data on age of pubertal events, forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1 ) at 26 years. Structural equation models were applied to examine mediation effects of DNAm on the association of age at pubertal events with FVC and FEV1 . Findings were further tested in the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort. Results: In the IOWBC, for females, 21 cytosine-phosphate-guanine sites (CpGs) were shown to mediate the association of age at puberty with FVC or FEV1 at 26 years (p<0.05). In males, DNAm at 20 CpGs was found to mediate the association of age at puberty with FVC (p<0.05). At almost all these CpGs, indirect effects (effects of age at pubertal events on FVC or FEV1 via DNAm) contributed a smaller portion to the total effects compared to direct effects ( e.g. at cg08680129, ∼22% of the estimated total effect of age at menarche on FVC at age 26 was contributed by an indirect effect). Among the IOWBC-discovered CpGs available in ALSPAC, none of them was replicated in ALSPAC (p>0.05). Conclusions: Our findings suggest that post-adolescence DNAm in peripheral blood is likely not to mediate the association of age at pubertal onset with young adulthood FVC or FEV1 . The association between age at pubertal onset and lung function parameters FVC or FEV1 in young adulthood is not likely to be mediated by DNA methylation in peripheral blood https://bit.ly/31G8hDi